Half yard kids sew 20 colourful toys and accessories from left-over pieces of fabric - Shore, Debbie (Tunbridge Well, Kent Search Press Limited, 2016)
The latest title from sewing guru Debbie Shore has arrived -- and it's her most fun yet! Packed with 20 colorful, inventive projects, it contains something for children of all ages. It contains a crafty fold-away easel for the young artist, a magnetic fishing game for the intrepid naturalist, and a colorful backpack for the young explorer. Why not make some spooky Halloween bunting to get ready for trick-or-treating, make a pirate cuddle pillow to decorate a swashbuckling bedroom, or just make up some funky monkey skittles for a game or two? Featuring Debbie's unique brand of friendly guidance, and packed with easy-to-follow photography, this book is ideal for beginners as well as providing inspiration to more experienced sewers, "--Amazon.com
Handcrafts
1
Keywords: Handicraft; Sewing; Soft toy making